Enhancing catalytic pyrolysis of polypropylene using mesopore-modified HZSM-5 catalysts: insights and strategies for improved performance - He, Qing; Akin, Oguzhan; Ureel, Yannick; Yazdani, Parviz; Li, Lingfeng; Varghese, Robin John; Van Geem, Kevin M. (Frontiers in Chemical Engineering, 2024)
Designing an active, selective, and stable catalyst for catalytic pyrolysis is crucial for its energy efficiency and economic viability. In this work, two mesopore introduction synthesis methods were employed to modify the physiochemical properties of CBV23, CBV55, and CBV80 zeolites, being NaOH and combined NaOH/CTAB treatments. Unlike the NaOH method, the NaOH/CTAB treatment preserves and enhances catalytic strong acid sites and results in a more uniform mesopore distribution. The catalytic performance of the parent and modified samples was evaluated using a two-stage micro-pyrolyzer coupled with a two-dimensional GC-FID/MS. The hierarchical CBV80-ZM, with optimized acidity, surface area, and mesopore distribution, shows excellent catalytic performance, achieving a high propylene yield of 41 wt.%. Furthermore, the total light olefins and MA yields using this catalyst reach 92 wt.%, effectively maximizing the production of high-value chemicals from PP pyrolysis. A detailed analysis of the reaction mechanism and zeolite properties revealed that the decreased weak acid site ratio and larger pore size were the cause for these high propylene yields. The obtained insights in this work regarding the effect of zeolite acidity and pore size distribution facilitate the design of tailored zeolites depending on their target product for the catalytic pyrolysis of propylene.